To find the values of \( g(x) \) based on the transformation of the function \( f(x) = -12x^2 + 21x - 3 \) through a horizontal stretch by a factor of \( k = 12 \), we first need to understand how the transformation affects the input values.
A horizontal stretch by a factor of \( k \) means that if we have a function \( f(x) \), the new function \( g(x) \) can be represented as:
\[ g(x) = f\left(\frac{x}{k}\right) = f\left(\frac{x}{12}\right) \]
We will use this to calculate \( g(0) \), \( g(1) \), and \( g(2) \) based on the values of \( f(x) \) from Table 1:
Calculating the values for \( g(x) \)
-
For \( g(0) \):
\[ g(0) = f\left(\frac{0}{12}\right) = f(0) \]
From Table 1: \[ f(0) = -3 \] So, \[ g(0) = -3 \]
-
For \( g(1) \):
\[ g(1) = f\left(\frac{1}{12}\right) \]
To find \( f\left(\frac{1}{12}\right) \), we substitute \( x = \frac{1}{12} \) into the function \( f(x) \):
\[ f\left(\frac{1}{12}\right) = -12\left(\frac{1}{12}\right)^2 + 21\left(\frac{1}{12}\right) - 3 \]
Calculating each term: \[ -12\left(\frac{1}{12}\right)^2 = -12\left(\frac{1}{144}\right) = -\frac{12}{144} = -\frac{1}{12} \]
\[ 21\left(\frac{1}{12}\right) = \frac{21}{12} = \frac{7}{4} \]
So, \[ f\left(\frac{1}{12}\right) = -\frac{1}{12} + \frac{7}{4} - 3 \]
Convert \(-3\) into twelfths: \[ -3 = -\frac{36}{12} \]
Now add these together: \[ -\frac{1}{12} + \frac{21}{12} - \frac{36}{12} = \frac{-1 + 21 - 36}{12} = \frac{-16}{12} = -\frac{4}{3} \]
Thus, \[ g(1) = -\frac{4}{3} \]
-
For \( g(2) \):
\[ g(2) = f\left(\frac{2}{12}\right) = f\left(\frac{1}{6}\right) \]
Substitute \( x = \frac{1}{6} \) into function \( f(x) \):
\[ f\left(\frac{1}{6}\right) = -12\left(\frac{1}{6}\right)^2 + 21\left(\frac{1}{6}\right) - 3 \]
Calculating each term: \[ -12\left(\frac{1}{6}\right)^2 = -12\left(\frac{1}{36}\right) = -\frac{12}{36} = -\frac{1}{3} \]
\[ 21\left(\frac{1}{6}\right) = \frac{21}{6} = \frac{7}{2} \]
So, \[ f\left(\frac{1}{6}\right) = -\frac{1}{3} + \frac{21}{6} - 3 \]
Convert \(-3\) into sixths: \[ -3 = -\frac{18}{6} \]
Now combine: \[ -\frac{1}{3} + \frac{21}{6} - \frac{18}{6} = -\frac{2}{6} + \frac{21}{6} - \frac{18}{6} = \frac{1}{6} \]
Thus, \[ g(2) = \frac{1}{6} \]
Finalizing Table 2
Now we can complete Table 2:
| x | g(x) | |---|-----------| | 0 | -3 | | 1 | -\(\frac{4}{3}\) | | 2 | \(\frac{1}{6}\) |
So the completed values for \( g(x) \) are:
- \( g(0) = -3 \)
- \( g(1) = -\frac{4}{3} \)
- \( g(2) = \frac{1}{6} \)